Editor’s Note Vol.6(2) & 7(1) - Alam, Mahmudul (Journal of Business and Technology (Dhaka), 2013)
DOI: http://dx.doi.org/10.3329/jbt.v6i2.14513 Journal of Business and Technology (Dhaka) VolVI, Issue02, (July-December, 2011) & VolVII, Issue-1 (January-June, 2012)